ENT 530 Business Modal Canvas: Dissh Sdn Bhd / Nabiha Ali Redza ... [et al.] - Ali Redza, Nabiha; Ali Redza, Nadia; Anuar, Wan Amelia Syahirah; Mohamed Hanapi, Hanis Hazirah; Mohamad, Rasyidah (2021)
Most of the people think to do certain business does not require a complete report of proposal, what the most people out there thinking is to have money in order to start up business. Yes, it is important to have money, but money will be destroyed by the bad idea or incomplete idea of business. Therefore, the purpose of this assignment to enhance our skills and increase our knowledge towards planning an idea on how to do the business. This Business Model Canvas is practically show us on how to develop the new idea and how to create a better flow of doing business or to helps us to get a loan or grant from financial institution. Moreover, the content of Business Model Canvas covered all parts of new start-up business to guide newcomers of industry to identified what is important the most. It also includes the analysis of the competitors SWOT to get an idea what is a real deal of the market in the same nature of business, at least we are aware before anything to be happened later in future. The content of Business Model Canvas such as key partner, key resources, revenue stream and all other key point is to guide us on how to interpret the market deals. The most important thing to put ourselves onto the real situation of the business. The analysis is to ensure we do not do anything wrong too much when we in the real situation. Business Model Canvas also a completed proposal of getting the loans or grants form financial institution because they need to see the idea of the business, is it a realistic and can give profit or not. Therefore, the great and complete Business Model Canvas can persuade the financial institution to gives you loan or grant.